Quartz light window for solar-blind ultraviolet detection enhancement and preparation method and application thereof

By constructing a gradient micro -nano structure cyclical array on the ends of the quartz blutin, the quantum efficiency and cathode sensitivity of the daily blind ultraviolet enhancer have been improved, and the problem of short detection distance in the existing technology has been solved. Highly clear detection effect.

CN119355856AActive Publication Date: 2025-01-24CHINA BUILDING MATERIALS ACADEMY CO LTD +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411430544.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-24
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

The existing sun-blind ultraviolet image enhancers have a short detection distance due to the low quantum efficiency of the cesium telluride photocathode, which limits its application and development.

Method used

Using quartz blinds with a micro -nano -structure function layer, by constructing a gradient micro -nano structure cyclical array on the outline surface, forming a micro -nano -structure function layer with a high refractive index, reducing the quartz window and the cathode cathode layer The interface reflection and scattering are improved to improve the pass rate and diffraction efficiency.

Benefits of technology

The cathode sensitivity of the sun-blind UV image intensifier is improved, achieving long-distance and high-definition detection effects, and meeting the demand for high-performance sun-blind UV detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119355856A_ABST
    Figure CN119355856A_ABST
Patent Text Reader

Abstract

The invention relates to a quartz light window for solar-blind ultraviolet detection enhancement and a preparation method and application thereof. The method comprises the following steps: etching a hollow body micro-nano structure periodic array with a gradually varied shape on the surface of an emergent end face of a solar-blind ultraviolet band high-transmittance quartz substrate, and cleaning to obtain a quartz element, plating a solar-blind ultraviolet high-transmittance thin film material on the surface of the emergent end surface of the obtained quartz element to serve as a filling material of a hollow body structure; and polishing the surface of the coated emergent end surface to obtain an embedded solid micro-nano structure periodic array functional layer with the period of 100-300nm, the thickness of 80-300nm and the duty ratio of more than or equal to 0.5, and cleaning to obtain the solar blind ultraviolet detection enhancement quartz light window with the micro-nano structure periodic array. The quantum efficiency of the solar blind ultraviolet image intensifier cesium telluride photocathode is improved by adopting the quartz optical window with the micro-nano structure functional layer, so that the sensitivity of the cathode is improved, and the purpose of long-distance and high-definition detection is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of optical element and micro-nano structure manufacturing, and specifically relates to a quartz light window for enhanced solar-blind ultraviolet detection, and a preparation method and application thereof. Background Art

[0002] Due to the strong absorption of ultraviolet rays by the ozone layer in the atmosphere, the radiation in the mid-ultraviolet band in the range of 200nm to 280nm in the solar radiation reaching the earth's surface is extremely weak. This band is called the "solar spectrum blind area" or "solar blind". Since there is almost no solar radiation in the solar blind band in the near-earth atmosphere and there is no interference from the solar background radiation, it is very conducive to the capture of external signals in this band. Since a large amount of solar blind ultraviolet radiation is generated by tail flames of aircraft, missiles, corona arc discharges, forest fires, etc., solar blind ultraviolet detection imaging technology has been widely studied and applied in many key fields such as military defense, aerospace, corona detection, fire warning, and ultraviolet optical communications.

[0003] At present, the solar-blind ultraviolet detection imaging technology mainly includes image intensified charge coupled devices (ICCD) and solid-state array sensors. Among them, solid-state array sensors are still in the technical research and development stage due to problems such as short detection distance, unstable process, and low resolution, and cannot reach the application level. The solar-blind ultraviolet ICCD technology has been applied in the military and industrial fields due to the advantages of low dark current, fast response speed, good stability, low false alarm rate, and mature process of solar-blind ultraviolet image intensifiers; however, due to the low quantum efficiency of the cesium telluride photocathode of the solar-blind ultraviolet image intensifier, the cathode sensitivity is low, which in turn leads to a short detection distance, which seriously limits its application and development. In order to make up for the low quantum efficiency of solar-blind ultraviolet cesium telluride photocathode, the commonly used technical means are: (1) by optimizing the preparation process of cesium telluride photocathode, the photogenerated electron escape rate of cesium telluride photocathode layer is improved; (2) by MCP material and process innovation, the multiplication number of photogenerated electrons in microchannel is increased; (3) by phosphor screen material and process innovation, the imaging brightness and clarity of electron bombardment phosphor screen is improved. Although the current technical means can help to improve the detection distance, the improvement effect is not significant and still cannot meet the needs of high-performance solar-blind ultraviolet detection. Summary of the invention

[0004] In view of this, the main purpose of the present invention is to provide a quartz optical window for day-blind ultraviolet detection enhancement and its preparation method and application. The technical problem to be solved is to improve the quantum efficiency of the cesium telluride photocathode of the day-blind ultraviolet image intensifier by adopting a quartz optical window with a micro-nano structure functional layer, thereby improving the cathode sensitivity and achieving the purpose of long-distance and high-definition detection.

[0005] The purpose of the present invention and the technical problem solved are achieved by adopting the following technical solutions. The present invention proposes a method for preparing a quartz window for enhanced solar-blind ultraviolet detection, comprising the following steps:

[0006] 1) etching a periodic array of hollow micro-nano structures with gradual morphology on the exit end face of a clean quartz substrate with high transmittance in the solar-blind ultraviolet band, and obtaining a clean quartz element with a periodic array of hollow micro-nano structures with neat edges after multiple ultrasonic cleaning;

[0007] 2) coating the output end surface of the quartz element obtained in step 1) with a solar-blind ultraviolet high-transmittance thin film material as a filling material for the hollow body structure;

[0008] 3) The output end face after coating in step 2) is polished to obtain a periodic array micro-nano structure functional layer with an embedded solid body morphology with a thickness of 80nm to 300nm, and then ultrasonically cleaned to obtain a quartz light window for day-blind ultraviolet detection enhancement with a periodic array of micro-nano structure.

[0009] Preferably, in the aforementioned method for preparing a quartz window for enhanced day-blind ultraviolet detection, in step 1), the refractive index of the quartz substrate at a wavelength of 250 nm is n=1.5, and the transmittance at a wavelength of 250 nm is ≥90%.

[0010] Preferably, in the aforementioned method for preparing a quartz window for enhanced solar-blind ultraviolet detection, in step 1), the periodic array of hollow micro-nano structures is distributed in a hexagonal close-packed or tetragonal close-packed manner.

[0011] Preferably, in the aforementioned method for preparing a quartz light window for enhanced day-blind ultraviolet detection, in step 1), the top of the morphology of the periodic array of hollow micro-nano structures faces the interior of the quartz substrate.

[0012] Preferably, in the aforementioned preparation method of the quartz light window for enhanced day-blind ultraviolet detection, in step 1), the periodic array of hollow micro-nano structures with a gradient morphology includes a plurality of micro-nano structure units, the morphology of the micro-nano structure units is conical, trapezoidal, Gaussian or cylindrical, the bottom projection contour of the micro-nano structure unit is circular, square or regular polygonal, the bottom projection circle radius / circumscribed circle radius is 50nm to 150nm, the top projection circle radius / circumscribed circle radius is less than or equal to 50nm, the period is 100nm to 300nm, the height / depth is 80nm to 300nm, and the duty cycle of the periodic array of micro-nano structures is greater than or equal to 0.5.

[0013] Preferably, in the aforementioned method for preparing a quartz window for enhanced solar-blind ultraviolet detection, in step 1), the ultrasonic cleaning includes conventional ultrasonic cleaning, acid-base alternating ultrasonic cleaning, and anhydrous ethanol / isopropanol ultrasonic cleaning.

[0014] Preferably, in the aforementioned method for preparing a quartz window for enhanced day-blind ultraviolet detection, in step 2), the refractive index of the thin film material is greater than the refractive index of the transparent substrate, and is transparent to ultraviolet rays at a working wavelength of 200nm to 280nm.

[0015] Preferably, in the aforementioned method for preparing a quartz window for enhanced day-blind ultraviolet detection, in step 2), the thin film material is selected from a thin film of magnesium oxide, hafnium oxide, aluminum oxide and zirconium oxide, or a composite film of at least two materials.

[0016] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures. The present invention proposes a quartz light window for enhancing day-blind ultraviolet detection, the quartz light window for enhancing day-blind ultraviolet detection comprises a quartz substrate, the quartz substrate has an incident end face for receiving and transmitting incident light and a corresponding exit end face, the exit end face of the quartz substrate has a periodic array of hollow micro-nano structures with a gradual morphology, the periodic array of micro-nano structures comprises a plurality of micro-nano structure units; the micro-nano structure units of the exit end face are filled with a transparent thin film material with a high refractive index to form a solid micro-nano structure periodic array.

[0017] Preferably, in the aforementioned quartz light window for enhanced day-blind ultraviolet detection, the morphology of the periodic array of hollow micro-nano structures is conical, trapezoidal, Gaussian or cylindrical, and the bottom projection contour on the plane is circular, square or regular polygonal, the bottom projection circle radius / circumscribed circle radius R is 50nm~150nm, the top projection circle radius / circumscribed circle radius r≤50nm, the period P is 100nm~300nm, the height / depth H is 80nm~300nm, and the duty cycle of the periodic array of micro-nano structures is ≥0.5.

[0018] Preferably, in the aforementioned quartz light window for enhanced day-blind ultraviolet detection, the material of the substrate is quartz optical quartz, whose refractive index at a wavelength of 250nm is 1.5, and its transmittance in the effective area of ​​200nm~280nm is ≥90%; the refractive index of the transparent film material is greater than the refractive index of the quartz substrate, and it is transparent to ultraviolet rays of the working wavelength of 200nm~280nm.

[0019] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures. An optical device proposed by the present invention includes a quartz light window for day-blind ultraviolet detection enhancement; the quartz light window for day-blind ultraviolet detection enhancement includes a quartz substrate, the quartz substrate has an incident end face for receiving and transmitting incident light and a corresponding exit end face, the exit end face of the quartz substrate has a micro-nano structure periodic array with a gradual morphology, the micro-nano structure periodic array includes a plurality of micro-nano structure units; the micro-nano structure units of the exit end face are filled with a transparent thin film material with a high refractive index to form a solid micro-nano structure periodic array.

[0020] Preferably, in the aforementioned optical device, the optical device is a solar-blind ultraviolet image intensifier.

[0021] By means of the above technical solution, the quartz window for enhanced solar-blind ultraviolet detection and its preparation method and application provided by the present invention have at least the following advantages:

[0022] The quartz light window for enhanced solar-blind ultraviolet detection provided by the present invention constructs a gradual micro-nano structure periodic array on the output end face to form a micro-nano structure functional layer with a high refractive index gradient, so as to reduce the interface reflection and scattering between the output end face of the quartz light window and the cesium telluride photocathode layer, improve the transmittance, and improve the diffraction efficiency, thereby achieving the purpose of anti-reflection enhancement, eliminating stray light, and improving the quantum efficiency of the cesium telluride photocathode in the wavelength range of 200nm to 280nm.

[0023] The transmission-type quartz optical element prepared by the method provided by the present invention is suitable for flattened and lightweight optical systems, and can be used as an optical window to improve the comprehensive performance of instruments and equipment of solar-blind ultraviolet image intensifiers, which is of great significance in promoting the application and development of optical detection and imaging technology.

[0024] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic cross-sectional view of a periodic array of micro-nano structures on the surface of the output end face of the present invention; wherein, 1-substrate, 2-micro-nano structure functional layer, 3-solid micro-nano structure, 4-incident end face, 5-output end face;

[0026] Figure 2 It is a side-view stereoscopic schematic diagram of a periodic array of micro-nano structures on the surface of the output end face of the present invention; wherein, 1 is a substrate, 2 is a micro-nano structure functional layer, and 3 is a solid micro-nano structure;

[0027] Figure 3It is a side-view stereoscopic schematic diagram of a conventional transmission optical element; wherein, 1-substrate;

[0028] Figure 4 Schematic diagram (top view) of the tetragonal close-packed periodic array micro-nano structure distribution of the present invention;

[0029] Figure 5 Schematic diagram (top view) of the distribution of the hexagonal close-packed periodic array micro-nano structure of the present invention;

[0030] Fig. 6A Schematic diagram of a conical micro-nano structural unit of the present invention (conical);

[0031] Figure 6B Schematic diagram of a conical micro-nano structure unit of the present invention (square cone);

[0032] Figure 6C Schematic diagram of a conical micro-nano structural unit (polygonal pyramid) of the present invention;

[0033] Fig. 7A Schematic diagram of a trapezoidal micro-nanostructure unit of the present invention (truncated cone);

[0034] Figure 7B Schematic diagram of a trapezoidal micro-nanostructure unit of the present invention (square trapezoidal);

[0035] Figure 7C Schematic diagram of a trapezoidal micro-nanostructure unit of the present invention (polygonal trapezoidal shape);

[0036] Fig. 8A Schematic diagram of a micro-nano structure unit of a Gaussian surface shape of the present invention (Gaussian surface shape);

[0037] Figure 8B Schematic diagram of the Gaussian surface micro-nano structure unit of the present invention (side projection of the Gaussian surface);

[0038] Figure 8C Schematic diagram of the Gaussian micro-nano structure unit of the present invention (side projection of the flat-top Gaussian surface);

[0039] Fig.9A Schematic diagram of a columnar micro-nano structural unit of the present invention (cylindrical);

[0040] Fig. 9B Schematic diagram of a columnar micro-nano structural unit of the present invention (square column);

[0041] Fig. 9C Schematic diagram of the columnar micro-nano structural unit of the present invention (polygonal column). DETAILED DESCRIPTION

[0042] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of a quartz window for enhanced solar-blind ultraviolet detection and its preparation method and application according to the present invention, its specific implementation method, structure, characteristics and effects, in combination with the preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.

[0043] The following materials or reagents, unless otherwise specified, were commercially available.

[0044] Some embodiments of the present invention provide a method for preparing a quartz window for enhanced solar-blind ultraviolet detection, comprising the following steps:

[0045] S1 uses a quartz substrate with high transmittance in the solar-blind ultraviolet band as a transparent substrate (refractive index n=1.5@250nm, transmittance ≥90%@250nm), and is ultrasonically cleaned in acetone, anhydrous ethanol, and deionized water in sequence to obtain a clean quartz substrate for use.

[0046] S2 uses the micro-nano structure precision processing technology commonly used in the semiconductor industry to etch a periodic array of hollow micro-nano structures with a gradual morphology on the surface of the output end of the above-mentioned quartz substrate, which is distributed in a hexagonal close-packed or tetragonal close-packed manner (such as Figure 4 and Figure 5 The hollow body micro-nano structure periodic array with gradual morphology includes a plurality of micro-nano structure units, and the micro-nano structure unit morphology is conical (as shown in FIG. Fig. 6A The cone shown, Figure 6B The square cone shown, Figure 6C The polygonal pyramid shown in the figure), the trapezoidal shape (such as Fig. 7A The truncated cone shown, Figure 7B The square shape shown, Figure 7C The polygonal pyramid shown in the figure), Gaussian surface (such as Fig. 8A , Figure 8B The conventional Gaussian shape shown, Figure 8C The flat-top Gaussian shape shown) or cylindrical shape (such as Fig.9A The cylindrical shape shown, Fig. 9B The square column shown, Fig. 9CThe micro-nano structure unit has a bottom projection profile of a circle, a square or a regular polygon, and its bottom projection circle radius / circumscribed circle radius R is 50nm to 150nm, the top projection circle radius / circumscribed circle radius r≤50nm, the period P is 100nm to 300nm, the height / depth H is 80nm to 300nm, and the duty ratio of the micro-nano structure periodic array is ≥0.5. The micro-nano structure precision machining includes etching, thin film deposition, and surface polishing of micro-nano scale structures. Etching mainly includes electron beam direct writing (EBL), inductively coupled plasma etching (ICP), ion beam etching (IBE), reactive ion beam etching (RIBE), etc. Thin film deposition mainly includes atomic layer deposition ALD, chemical vapor deposition CVD, magnetron sputtering coating, electron beam evaporation coating, laser pulse evaporation coating, etc. Surface polishing mainly includes chemical mechanical polishing CMP, plasma etching polishing, mechanical double-sided polishing, mechanical single-sided polishing, etc.

[0047] After S3 etching is completed, concentrated sulfuric acid, hydrogen peroxide, and deionized water (to remove photoresist) are used as needed. Concentrated sulfuric acid with a concentration of 90wt% and hydrogen peroxide with a concentration of 30vol% are mixed in a volume ratio of 1:2, and ultrasonic cleaning (power of 28kHz) is performed for 20 minutes. The ultrasonic cleaning is repeated 3 times to remove the photoresist.

[0048] S4 is then cleaned by alternating acid-base ultrasonic cleaning with dilute hydrofluoric acid, sodium hydroxide solution (which can corrode and remove quartz burrs and improve the surface morphology of the substrate); diluted hydrofluoric acid solution (concentration of 0.01vol% to 0.5vol%), and diluted strong alkali solution (concentration of 0.05vol% to 3vol%), using the acid-base alternating method to further improve the etching morphology, and then ultrasonic cleaning with anhydrous ethanol / isopropanol to finally obtain a clean optical element with a periodic array of micro-nano structures with neat hollow body morphology. The process parameters of the ultrasonic cleaning include: an ultrasonic frequency of 80kHz, a temperature of 30°C, and an ultrasonic time generally ranging from 1 minute to 10 minutes.

[0049] S5 uses vacuum thin film preparation technology to plate a day-blind ultraviolet high-transmittance thin film material on the surface of the output end face of the above optical element as the filling material of the hollow body structure. The refractive index of the thin film material must be greater than the refractive index of the transparent substrate and have high transmittance to the working band (200nm~280nm). The thin film material can be selected from magnesium oxide, hafnium oxide, aluminum oxide, and zirconium oxide high-refractive index and high-transmittance ultraviolet thin films or a composite film of at least two materials. The four thin film materials of magnesium oxide, hafnium oxide, aluminum oxide, and zirconium oxide are selected because they have higher transmittance to day-blind ultraviolet and higher refractive index than the quartz substrate.

[0050] S6: polishing the surface of the output end face after the coating by conventional polishing technology, removing the excess film material by polishing, and obtaining a periodic array micro-nano structure functional layer with an embedded solid body morphology with a thickness of 80nm to 300nm.

[0051] After S7 polishing, ultrasonic cleaning is performed to remove contaminants in the processing flow, and a new type of surface micro-nanostructure transmission optical element with periodic arrays of micro-nanostructures on both end faces is obtained. The micro-nanostructure at the incident end has no filling material, and the micro-nanostructure at the output end is filled with a transparent film material with a higher refractive index.

[0052] In the above technical scheme, a sub-micron-scale micro-nanostructure functional layer with a gradient refractive index is constructed on the output end face, and the micro-nanostructure morphology and its structural distribution are utilized to reduce the reflection and scattering of day-blind ultraviolet light at the interface between the optical window and the photocathode, improve the day-blind ultraviolet transmittance and diffraction efficiency, and thereby improve the photon absorption and quantum efficiency of the photocathode layer. This is used as the optical window of a day-blind ultraviolet image intensifier, which can significantly improve the cathode sensitivity of the day-blind ultraviolet image intensifier, thereby enhancing the long-distance, high-definition detection capability of instruments and equipment related to the day-blind ultraviolet image intensifier, to meet the high-end needs of related fields.

[0053] In some embodiments, optionally, a micro-nano structure functional layer with a gradient high refractive index is prepared on the output end face of the quartz substrate, and the functional layer is composed of a periodic array of micro-nano structures with a gradient high refractive index embedded on the surface of the output end face of the quartz substrate. The micro-nano structure units of the embedded periodic array are solid bodies, and gradually increase in size along the output direction (e.g. Figure 2 The micro-nano structural unit is filled with a transparent film material, whose refractive index must be greater than that of the substrate and has high transmittance to the solar-blind band (200nm-280nm). A film of magnesium oxide, hafnium oxide, aluminum oxide and zirconium oxide or a composite film of at least two of them can be selected; the depth / height of the micro-nano structural unit is the thickness of the functional layer.

[0054] In some embodiments, optionally, the periodic arrays of micro-nano structures on the above-mentioned two end surfaces are hexagonal close-packed or tetragonal close-packed, the period P of the periodic array is 100nm~300nm, the height / depth of the micro-nano structure unit is 80nm~300nm, the duty cycle of the micro-nano structure periodic array is ≥0.5, the morphology of the micro-nano structure unit is conical, trapezoidal, Gaussian or cylindrical, the bottom projection contour of the micro-nano structure unit is circular, square, or regular polygon, the bottom projection circle radius / circumscribed circle radius R is 50nm~150nm, and the top projection circle radius / circumscribed circle radius r≤50nm.

[0055] The preferred period P is 100nm to 180nm; when P is less than 100nm, the transmission diffraction of the long-wave portion of the day-blind ultraviolet light close to 280nm is evanescent, causing a limited increase in the total optical path of photons in the photocathode layer, resulting in low quantum efficiency; when P is greater than 180nm, the reflection diffraction of the day-blind ultraviolet at the photocathode interface is significantly enhanced, causing an increase in reflectivity and a limited increase in transmittance, resulting in low quantum efficiency, and at the same time causing an increase in the transmission diffraction of long-wave ultraviolet outside the day-blind ultraviolet range, resulting in enhanced interference from extra-spectral light and reduced accuracy of day-blind ultraviolet detection.

[0056] Some embodiments of the present invention further provide a quartz light window for enhanced solar-blind ultraviolet detection, the quartz light window for enhanced solar-blind ultraviolet detection comprising a quartz substrate 1, the quartz substrate 1 having an incident end face 4 for receiving and transmitting incident light and an opposite exit end face 5, the exit end face 5 of the quartz substrate 1 having a micro-nano structure periodic array functional layer 2 with a gradually changing morphology, the micro-nano structure periodic array functional layer 2 comprising a plurality of micro-nano structure units 3; the micro-nano structure units 3 are filled with a solar-blind ultraviolet transparent thin film material with a high refractive index to form a solid micro-nano structure periodic array, see Figure 1 .

[0057] The quartz substrate 1 is used as the base material of the light window because quartz has the advantages of high transmittance to solar-blind ultraviolet, resistance to environmental corrosion, high mechanical strength, low price, and easy procurement. It is also an optical material commonly used in the field of solar-blind ultraviolet detection applications.

[0058] The preparation of the micro-nano structure functional layer on the output end face of the quartz substrate 1 is mainly due to two factors. One is that the refractive index of the cesium telluride photocathode for the current day-blind ultraviolet is much higher than that of quartz, resulting in a large reflectivity between the photocathode and quartz. Therefore, it is necessary to prepare a functional layer with a gradually increasing refractive index on the quartz output end face to reduce the refractive index deviation between the quartz and the cesium telluride photocathode, thereby reducing the reflectivity and improving the day-blind ultraviolet transmittance. The second is that the current conventional quartz light window does not have a micro-nano structure, and the day-blind ultraviolet light directly penetrates into the photocathode for photoelectric conversion. Due to the short direct transmission optical path, the photoelectric conversion efficiency is low; by preparing a micro-nano structure functional layer of suitable size specifications on the quartz output end face, the penetrating day-blind ultraviolet light is diffracted and interfered, the transmission direction is deflected, the transmission optical path is increased, and the photoelectric conversion efficiency is significantly improved, thereby improving the cathode sensitivity.

[0059] It can be seen from this that the micro-nanostructure functional layer must be located between the quartz and the photocathode, the gradient refractive index must gradually increase along the transmission direction of the solar-blind ultraviolet light, and the size specifications must meet the requirements of solar-blind ultraviolet working.

[0060] First, a solid periodic array of micro-nano structures is constructed on the output end face 5 of the quartz substrate 1. There are two main purposes. One is to realize a refractive index gradient functional layer from the quartz substrate to the output end face through a micro-nano structure with a gradient morphology from the top toward the substrate, so as to reduce the interface reflectivity between the output end face and the cesium telluride photocathode layer and improve the solar-blind ultraviolet transmittance; the other is to control the diffraction of solar-blind ultraviolet transmitted light by constructing a periodic array of micro-nano structures of appropriate size, increase the diffraction optical path and diffraction light ratio of solar-blind ultraviolet transmission into the cesium telluride photocathode layer, and thereby improve the quantum efficiency of the cesium telluride photocathode layer.

[0061] In the above technical scheme, the present invention constructs a gradient high-refractive-index micro-nano structure array on the surface of its output end face, and utilizes the micro-nano structure morphology and its structural distribution design to reduce light reflection and scattering at the interface between the quartz window and the cesium telluride photocathode, improve the day-blind ultraviolet transmittance and diffraction efficiency on the interface, thereby improving the cesium telluride quantum efficiency and achieving high cathode sensitivity. It can be used as an optical window to improve the comprehensive performance of related instruments and equipment such as day-blind ultraviolet image intensifiers, and meet the high-end needs of related fields.

[0062] The above-mentioned quartz window for enhanced solar-blind ultraviolet detection is used as an optical window to make a cesium telluride photocathode. After testing, the interface reflectivity at 250nm is reduced to 1.9%-5.5%, the transmittance is increased to 91.7%-95.3%, and the quantum efficiency is increased to 23%-31%. Compared with conventional quartz optical windows, its interface reflectivity is reduced by 50%-81%, the transmittance is increased by 1.89%-5.89%, and the quantum efficiency is increased by 27.8%-72.2%.

[0063] In some embodiments, optionally, the top of the solid micro-nano structure periodic array of the input and output end faces faces the inside of the quartz substrate. The output end is a solid body morphology, and the solid body morphology, that is, the structure morphology is filled with a high-transmittance ultraviolet thin film material with a higher refractive index than the quartz substrate. Because the cesium telluride photocathode material is evaporated on the output end face of the quartz substrate, when the top of the structure morphology faces the inside of the quartz substrate, a refractive index gradient functional layer from the quartz substrate to the cesium telluride photocathode layer is formed to reduce the interface refractive index mutation, so as to achieve the purpose of reducing reflection and improving transmission of the quartz light window / cesium telluride photocathode interface output light (transmitted light).

[0064] In some embodiments, optionally, the morphology of the periodic array of micro-nano structures is a cone, a trapezoid, a Gaussian surface or a column, and the bottom projection contour on the plane is a circle, a square or a regular polygon, wherein the cone, the trapezoid and the Gaussian surface are all gradient morphologies with inconsistent sizes between the top and the bottom, and the column is a morphology with consistent sizes between the top and the bottom. By constructing the above-mentioned periodic array of micro-nano structures on the output end face of the quartz substrate, a refractive index transition effect can be constructed on the interface between the quartz light window and the cesium telluride photocathode. The bottom profile of the micro-nano structure is circular, square or regular polygonal, and such a shape is proposed in combination with hexagonal close packing or tetragonal close packing, and the purpose is to achieve uniform diffraction of the transmitted light on the above-mentioned interface; the period P of the structure is 100nm to 300nm, and the period is considered from the diffraction effect of the light in the 200-280nm band; when the period is less than 100nm, the transmission diffraction of the light in the 200-280nm band almost disappears and the diffraction efficiency is poor, resulting in the effect of increasing the optical path of the transmitted light in the cesium telluride photocathode layer is not obvious, and ultimately leads to low quantum efficiency; when the period is greater than 300nm, the interface reflection diffraction of the light in the 200-280nm band is enhanced, the reflectivity is large, the scattering is strong, the overall transmittance is poor, and multiple diffraction occurs, the diffraction efficiency is low, resulting in a decrease in the total number of photons transmitted into the cesium telluride photocathode layer and a decrease in the total optical path, which ultimately leads to low quantum efficiency. The duty cycle of the bottom projection contour is ≥0.5. The larger the duty cycle, the better the refractive index gradient effect, the smoother the refractive index drop transition between the quartz window and the cesium telluride photocathode, and the lower the interface reflectivity caused. When the duty cycle is less than 0.5, the refractive index gradient effect is poor, and the maximum duty cycle is 1.0, so the duty cycle of the micro-nano structure periodic array is ≥0.5. The bottom projection circumscribed circle radius is determined according to the duty cycle range. The circumscribed circle radius of the bottom projection is 50nm to 150nm. When the duty cycle is 0.5, for a period of 100nm, the bottom projection circumscribed circle radius is 50nm; when the duty cycle is 1.0, for a period of 300nm, the bottom projection circumscribed circle radius is 150nm. The radius of the circumscribed circle of the top projection is ≤20nm, and the smaller the top is, the better the refractive index gradient effect is; when the radius of the circumscribed circle of the top projection is greater than 20nm, the refractive index gradient effect is significantly deteriorated; its height / depth is 80nm~300nm, and the height / depth of the structure is to reduce the interface reflectivity while taking into account the diffraction efficiency of the transmitted light in the cesium telluride photocathode layer to achieve a high level, thereby achieving a higher quantum efficiency.The structure height / depth is related to the period and the working wavelength. Generally, the structure height / depth is comparable to the period, but the larger the structure height / depth, the more obvious the reduction in interface reflectivity. At the same time, because the transmission diffraction efficiency is related to the working wavelength (200-280nm), the structure height / depth is generally required to be in the range of 0.4 to 1.1 times the working wavelength for the day-blind ultraviolet band. When the structure height / depth is too large or too small, the diffraction efficiency will be significantly reduced. Therefore, the structure height / depth is set to 80nm~300nm based on comprehensive considerations.

[0065] In some embodiments, optionally, the morphologies of the plurality of micro-nanostructure units are the same; the periodic array must have the same and orderly morphological specifications. Only by forming a periodic array can there be a light diffraction effect that is regularly controllable and uniformly distributed overall.

[0066] In some embodiments, optionally, the material of the quartz substrate is quartz optical glass, and its refractive index is 1.5 (the refractive index involved in the present invention refers to the refractive index value corresponding to the day-blind ultraviolet light with a wavelength of 250nm), and its transmittance in the effective area of ​​200nm to 280nm is ≥90%; the refractive index of the transparent film material must be greater than the refractive index of the quartz substrate, and it has high transmittance to the ultraviolet light with a working wavelength of 200nm to 280nm. The transparent film material is a material filled in the micro-nano structure morphology of the output end face, and the purpose is to construct a micro-nano structure functional layer with a gradual refractive index of the output end face. In view of this, when screening the film material, it is necessary to consider whether the refractive index of the film material is greater than the refractive index of the quartz substrate used, whether the transmission spectrum range of the film material conforms to the working wavelength range, whether the transmittance of the film material in the working band range is high, and whether the film material has a stable and feasible film preparation plan.

[0067] Some embodiments of the present invention further provide an optical device, which includes the above-mentioned quartz light window for day-blind ultraviolet detection enhancement. The quartz light window of the present invention is only suitable for light signal detection enhancement in the day-blind ultraviolet band, and is not suitable for light signal detection enhancement in other bands, because the size specifications and material selection of the micro-nanostructure functional layer need to be customized according to the specific working wavelength range, and are not universally applicable.

[0068] In some embodiments, the optical device is optionally a solar-blind ultraviolet image intensifier. The present invention is applicable to currently known solar-blind ultraviolet image intensifiers, and may also be applicable to other detection optical devices in the solar-blind ultraviolet working band, which needs to be determined according to the specific conditions of other devices.

[0069] The present invention is further described below in conjunction with specific embodiments.

[0070] Embodiment 1:

[0071] S1 uses a quartz substrate of Ф18*3mm (refractive index n=1.5@250nm) as a transparent substrate, and is cleaned by acetone, anhydrous ethanol, and deionized water ultrasonically (power is 45kHz) for 5 minutes each, and the cleaning is repeated 3 times to obtain a clean quartz substrate for use.

[0072] S2 uses electron beam direct writing (EBL) technology to etch a conical hollow body hexagonal close-packed micro-nano structure periodic array on the output end surface of the above quartz substrate, with the top of the cone facing the inside of the quartz (such as Figure 5 , as shown in FIG6). The operating parameters of the electron beam direct writing technology are as follows: the working vacuum degree is 5×10 -4 Pa, the maximum acceleration voltage is 150kV, the scanning main frequency is 12MHz, the scanning step is 2nm, and the minimum beam spot is 3nm. The conical micro-nano structure periodic array includes a plurality of conical micro-nano structure units, and the etched period P is 160nm, the duty cycle is 0.625, the depth / height of the structure unit is 110nm, and the radius of the circumscribed circle of the bottom projection is 50nm.

[0073] After S3 etching is completed, the samples are ultrasonically cleaned (with a power of 80kHz) with acetone, anhydrous ethanol, and deionized water for 5 minutes each, and the ultrasonic cleaning is repeated 3 times (to clean the organic contamination, grease, and dust contamination that the samples have been exposed to during circulation and operation).

[0074] S4 was then cleaned with 0.01 vol% dilute hydrofluoric acid, 0.1 wt% sodium hydroxide solution, and anhydrous ethanol, each with ultrasound (power of 80 kHz) for 1 minute, and repeated ultrasound for 3 times (chemical corrosion method of alternating acid and alkali erosion to assist in further improving the etching morphology), and finally a periodic array of micro-nano structures with neatly edged conical hollow bodies was obtained.

[0075] S5 uses atomic layer deposition (ALD) technology to plate a magnesium oxide film on the surface of the above-mentioned output end face as the filling material of the conical hollow body micro-nano structure, and uses bis(cyclopentadienyl)magnesium (Mg(C 5 H 5 ) 2 ) as a precursor, H 2 O as reactant, N 2 With N 2 O 4 as carrier gas, reaction temperature of 200° C. and growth rate of 0.1 nm / cycle, a magnesium oxide film with a thickness of 160 nm and a refractive index of 1.8@250 nm was grown.

[0076] S6 uses chemical mechanical polishing technology to polish the surface of the output end face after the above coating, and the process parameters used are a speed of 70rpm and a pressure of 6g / mm 2The polishing liquid flow rate is 2 mL / min, and the excess magnesium oxide film layer is polished to obtain a periodic array micro-nano structure functional layer 2 of embedded conical solid bodies filled with magnesium oxide with a thickness of 110 nm, such as Figure 2 As shown, the micro-nano structure periodic array functional layer 2 includes a plurality of micro-nano structure units 3; the micro-nano structure units 3 are filled with magnesium oxide to form a solid micro-nano structure periodic array.

[0077] After S7 polishing, the sample was cleaned with acetone, anhydrous ethanol, and deionized water ultrasonically (power of 45kHz) for 5 minutes each, and the cleaning was repeated 3 times (cleaning to remove organic matter, dust, particles and other contaminations on the sample during the circulation and operation process), and a surface micro-nanostructure transmission quartz optical element with a periodic array of conical micro-nanostructures filled with magnesium oxide thin film materials at the output end was obtained; wherein the radius of the circumscribed circle of the bottom of the cone is 50nm, the period P is 160nm, and the height / depth is 110nm.

[0078] The surface micro-nanostructured transmission quartz optical element is used as an optical window to make a cesium telluride photocathode. Compared with conventional quartz optical windows (such as Figure 3 As shown, it includes substrate 1a), its interface reflectivity @250nm is reduced by 61%, transmittance @250nm is increased by 3.56%, and quantum efficiency is increased by 50%, see Table 1.

[0079] Embodiment 2:

[0080] S1 uses a quartz substrate (n=1.5@250nm) of Φ18*3mm as a transparent substrate, and is cleaned by ultrasonic cleaning (power of 45kHz) of acetone, anhydrous ethanol, and deionized water for 5 minutes each, and the cleaning is repeated 3 times to obtain a clean quartz substrate for use.

[0081] S2 uses electron beam direct writing (EBL) technology to etch a conical hollow body hexagonal close-packed micro-nano structure periodic array on the output end surface of the above quartz substrate, with the top of the cone facing the inside of the quartz (such as Figure 5 , Fig. 6A The operating parameters of the electron beam direct writing technology are as follows: the working vacuum degree is 5×10 -4 Pa, the maximum acceleration voltage is 150kV, the scanning main frequency is 12MHz, the scanning step is 2nm, and the minimum beam spot is 3nm. The conical micro-nano structure periodic array includes a plurality of conical micro-nano structure units, and the etched period P is 160nm, the duty cycle is 0.625, the depth / height of the structure unit is 300nm, and the radius of the circumscribed circle of the bottom projection is 50nm.

[0082] After S3 etching is completed, the samples are cleaned with acetone, anhydrous ethanol, and deionized water ultrasonically (power is 80kHz) for 5 minutes each, and the ultrasonic cleaning is repeated 3 times (to clean the organic pollution, grease, and dust pollution caused by the sample during the circulation and operation process);

[0083] S4 was then cleaned with 0.01 vol% dilute hydrofluoric acid, 0.1 wt% sodium hydroxide solution, and anhydrous ethanol, each with ultrasound (power of 80 kHz) for 1 minute, and repeated ultrasound for 3 times (chemical corrosion method of alternating acid and alkali erosion to assist in further improving the etching morphology), and finally a periodic array of micro-nano structures with neatly edged conical hollow bodies was obtained.

[0084] S5 uses atomic layer deposition (ALD) technology to plate a magnesium oxide film on the surface of the above-mentioned output end face as the filling material of the conical hollow body micro-nano structure, and uses bis(cyclopentadienyl)magnesium (Mg(C 5 H 5 ) 2 ) as a precursor, H 2 O as reactant, N 2 With N 2 O 4 as carrier gas, reaction temperature of 200° C. and growth rate of 0.1 nm / cycle, a magnesium oxide film with a thickness of 350 nm and a refractive index of 1.8@250 nm was grown.

[0085] S6 uses chemical mechanical polishing technology to polish the surface of the output end face after the above coating, and the process parameters used are a speed of 70rpm and a pressure of 6g / mm 2 The polishing liquid flow rate is 2 mL / min, and the excess magnesium oxide film layer is polished to obtain a periodic array micro-nano structure functional layer 2 of embedded conical solid bodies filled with magnesium oxide with a thickness of 110 nm, such as Figure 2 As shown, the micro-nano structure periodic array functional layer 2 includes a plurality of micro-nano structure units 3; the micro-nano structure units 3 are filled with magnesium oxide to form a solid micro-nano structure periodic array.

[0086] After S7 polishing is completed, the sample is cleaned with acetone, anhydrous ethanol, and deionized water ultrasonically (power is 45kHz) for 5 minutes each, and the cleaning is repeated 3 times (cleaning removes organic matter, dust, particles and other contaminations that the sample is exposed to during the circulation and operation process), and a surface micro-nanostructure transmission quartz optical element with a periodic array of conical micro-nanostructures filled with magnesium oxide thin film materials at the output end is obtained; wherein the radius of the circumscribed circle of the bottom of the cone is 50nm, the period P is 160nm, and the height / depth is 300nm.

[0087] The surface micro-nanostructured transmission quartz optical element is used as an optical window to make a cesium telluride photocathode. Compared with conventional quartz optical windows (such as Figure 3As shown, it includes a substrate 1a), whose interface reflectivity @250nm is reduced by 65%, the transmittance @250nm is increased by 3.89%, and the quantum efficiency is increased by 44.4%.

[0088] Embodiment 3:

[0089] S1 uses a quartz substrate (n=1.5@250nm) of Φ18*3mm as a transparent substrate, and is cleaned by ultrasonic cleaning (power of 45kHz) of acetone, anhydrous ethanol, and deionized water for 5 minutes each, and the cleaning is repeated 3 times to obtain a clean quartz substrate for use.

[0090] S2 uses electron beam direct writing (EBL) technology to etch a conical hollow body hexagonal close-packed micro-nano structure periodic array on the output end surface of the above quartz substrate, with the top of the cone facing the inside of the quartz (such as Figure 5 , Fig. 6A The operating parameters of the electron beam direct writing technology are as follows: the working vacuum degree is 5×10 -4 Pa, the maximum acceleration voltage is 150kV, the scanning main frequency is 12MHz, the scanning step is 2nm, and the minimum beam spot is 3nm. The conical micro-nano structure periodic array includes a plurality of conical micro-nano structure units, and the etched period P is 160nm, the duty cycle is 0.625, the depth / height of the structure unit is 80nm, and the radius of the circumscribed circle of the bottom projection is 50nm.

[0091] After S3 etching is completed, the samples are cleaned with acetone, anhydrous ethanol, and deionized water ultrasonically (power is 80kHz) for 5 minutes each, and the ultrasonic cleaning is repeated 3 times (to clean the organic pollution, grease, and dust pollution caused by the sample during the circulation and operation process);

[0092] S4 was then cleaned with 0.01 vol% dilute hydrofluoric acid, 0.1 wt% sodium hydroxide solution, and anhydrous ethanol, each with ultrasound (power of 80 kHz) for 1 minute, and repeated ultrasound for 3 times (chemical corrosion method of alternating acid and alkali erosion to assist in further improving the etching morphology), and finally a periodic array of micro-nano structures with neatly edged conical hollow bodies was obtained.

[0093] S5 uses atomic layer deposition (ALD) technology to plate a magnesium oxide film on the surface of the above-mentioned output end face as the filling material of the conical hollow body micro-nano structure, and uses bis(cyclopentadienyl)magnesium (Mg(C 5 H 5 ) 2 ) as a precursor, H 2 O as reactant, N 2With N 2 O 4 as carrier gas, reaction temperature of 200° C. and growth rate of 0.1 nm / cycle, a magnesium oxide film with a thickness of 150 nm and a refractive index of 1.8@250 nm was grown.

[0094] S6 uses chemical mechanical polishing technology to polish the surface of the output end face after the above coating, and the process parameters used are a speed of 70rpm and a pressure of 6g / mm 2 The polishing liquid flow rate is 2 mL / min, and the excess magnesium oxide film layer is polished to obtain a periodic array micro-nano structure functional layer 2 of embedded conical solid bodies filled with magnesium oxide with a thickness of 110 nm, such as Figure 2 As shown, the micro-nano structure periodic array functional layer 2 includes a plurality of micro-nano structure units 3; the micro-nano structure units 3 are filled with magnesium oxide to form a solid micro-nano structure periodic array.

[0095] After S7 polishing, the sample was cleaned with acetone, anhydrous ethanol, and deionized water ultrasonically (power of 45kHz) for 5 minutes each, and the cleaning was repeated 3 times (cleaning to remove organic matter, dust, particles and other contaminants that the sample was exposed to during the circulation and operation process), and a surface micro-nanostructure transmission quartz optical element with a periodic array of conical micro-nanostructures filled with magnesium oxide thin film materials at the output end was obtained; wherein the radius of the circumscribed circle of the bottom of the cone is 50nm, the period P is 160nm, and the height / depth is 80nm.

[0096] The surface micro-nanostructured transmission quartz optical element is used as an optical window to make a cesium telluride photocathode. Compared with conventional quartz optical windows (such as Figure 3 As shown, it includes substrate 1a), its interface reflectivity @250nm is reduced by 59%, the transmittance @250nm is increased by 3.33%, and the quantum efficiency is increased by 38.9%.

[0097] Embodiment 4:

[0098] S1 uses a quartz substrate (n=1.5@250nm) of Φ18*3mm as a transparent substrate, and is cleaned by ultrasonic cleaning (power of 45kHz) of acetone, anhydrous ethanol, and deionized water for 5 minutes each, and the cleaning is repeated 3 times to obtain a clean quartz substrate for use.

[0099] S2 uses electron beam direct writing (EBL) technology to etch a conical hollow body hexagonal close-packed micro-nano structure periodic array on the output end surface of the above quartz substrate, with the top of the cone facing the inside of the quartz (such as Figure 5 , Fig. 6A The operating parameters of the electron beam direct writing technology are as follows: the working vacuum degree is 5×10 -4Pa, the maximum acceleration voltage is 150kV, the scanning main frequency is 12MHz, the scanning step is 2nm, and the minimum beam spot is 3nm. The conical micro-nano structure periodic array includes a plurality of conical micro-nano structure units, and the etched period P is 160nm, the duty cycle is 1, the depth / height of the structure unit is 110nm, and the radius of the circumscribed circle of the bottom projection is 80nm.

[0100] After S3 etching is completed, the samples are cleaned with acetone, anhydrous ethanol, and deionized water ultrasonically (power is 80kHz) for 5 minutes each, and the ultrasonic cleaning is repeated 3 times (to clean the organic pollution, grease, and dust pollution caused by the sample during the circulation and operation process);

[0101] S4 was then cleaned with 0.01 vol% dilute hydrofluoric acid, 0.1 wt% sodium hydroxide solution, and anhydrous ethanol, each with ultrasound (power of 80 kHz) for 1 minute, and repeated ultrasound for 3 times (chemical corrosion method of alternating acid and alkali erosion to assist in further improving the etching morphology), and finally a periodic array of micro-nano structures with neatly edged conical hollow bodies was obtained.

[0102] S5 uses atomic layer deposition (ALD) technology to plate a magnesium oxide film on the surface of the above-mentioned output end face as the filling material of the conical hollow body micro-nano structure, and uses bis(cyclopentadienyl)magnesium (Mg(C 5 H 5 ) 2 ) as a precursor, H 2 O as reactant, N 2 With N 2 O 4 as carrier gas, reaction temperature of 200° C. and growth rate of 0.1 nm / cycle, a magnesium oxide film with a thickness of 160 nm and a refractive index of 1.8@250 nm was grown.

[0103] S6 uses chemical mechanical polishing technology to polish the surface of the output end face after the above coating, and the process parameters used are a speed of 70rpm and a pressure of 6g / mm 2 The polishing liquid flow rate is 2 mL / min, and the excess magnesium oxide film layer is polished to obtain a periodic array micro-nano structure functional layer 2 of embedded conical solid bodies filled with magnesium oxide with a thickness of 110 nm, such as Figure 2 As shown, the micro-nano structure periodic array functional layer 2 includes a plurality of micro-nano structure units 3; the micro-nano structure units 3 are filled with magnesium oxide to form a solid micro-nano structure periodic array.

[0104] After S7 polishing, the sample was cleaned with acetone, anhydrous ethanol, and deionized water ultrasonically (power of 45kHz) for 5 minutes each, and the cleaning was repeated 3 times (cleaning to remove organic matter, dust, particles and other contaminants that the sample was exposed to during the circulation and operation process), and a surface micro-nanostructure transmission quartz optical element with a periodic array of conical micro-nanostructures filled with magnesium oxide thin film materials at the output end was obtained; wherein the radius of the circumscribed circle of the bottom of the cone is 80nm, the period P is 160nm, and the height / depth is 110nm.

[0105] The surface micro-nanostructured transmission quartz optical element is used as an optical window to make a cesium telluride photocathode. Compared with conventional quartz optical windows (such as Figure 3 As shown, it includes substrate 1a), its interface reflectivity @250nm is reduced by 77%, transmittance @250nm is increased by 4.78%, and quantum efficiency is increased by 61.1%, see Table 1.

[0106] Comparative Example 1:

[0107] According to the preparation steps of Example 4, only the period P of the micro-nano structure is changed to 600nm and the depth / height of the structural unit is changed to 350nm, and other parameters remain unchanged (duty cycle is 1), and the corresponding radius of the circumscribed circle of the bottom projection is 300nm, and a periodic array micro-nano structure functional layer 2 of embedded conical solid bodies filled with magnesium oxide with a period P of 600nm, a duty cycle of 1, a depth / height of the structural unit of 350nm, is obtained, as shown in Figure 2 As shown, the micro-nano structure periodic array functional layer 2 includes a plurality of micro-nano structure units 3; the micro-nano structure units 3 are filled with magnesium oxide to form a solid micro-nano structure periodic array.

[0108] The surface micro-nanostructured transmission quartz optical element is used as an optical window to make a cesium telluride photocathode. Compared with conventional quartz optical windows (such as Figure 3 As shown, it includes substrate 1a), its interface reflectivity @250nm is reduced by 40%, transmittance @250nm is increased by 1.11%, and quantum efficiency is only increased by 2.8%, which cannot meet the needs of high-performance day-blind ultraviolet detection, see Table 1.

[0109] Comparative Example 2:

[0110] According to the preparation steps of Example 4, only the period P of the micro-nano structure is changed to 60nm, and other parameters remain unchanged (duty cycle is 1, depth / height of the structural unit is 110nm), and the corresponding radius of the circumscribed circle of the bottom projection is 30nm, and a periodic array micro-nano structure functional layer 2 of embedded conical solid bodies filled with magnesium oxide with a period P of 60nm, a duty cycle of 1, a depth / height of the structural unit of 110nm is obtained, as shown in Figure 2As shown, the micro-nano structure periodic array functional layer 2 includes a plurality of micro-nano structure units 3; the micro-nano structure units 3 are filled with magnesium oxide to form a solid micro-nano structure periodic array.

[0111] The surface micro-nanostructured transmission quartz optical element is used as an optical window to make a cesium telluride photocathode. Compared with conventional quartz optical windows (such as Figure 3 As shown, it includes substrate 1a), its interface reflectivity @250nm is reduced by 44%, transmittance @250nm is increased by 1.67%, and quantum efficiency is only increased by 3.3%, which cannot meet the needs of high-performance day-blind ultraviolet detection, see Table 1.

[0112] Embodiment 5:

[0113] S1 uses a quartz substrate (n=1.5@250nm) of Φ40*5mm as a transparent substrate, and is cleaned by ultrasonic cleaning (power of 45kHz) of acetone, anhydrous ethanol, and deionized water for 5 minutes each, and the cleaning is repeated 3 times to obtain a clean quartz substrate for use.

[0114] S2 uses electron beam direct writing (EBL) technology to etch a conical hollow body hexagonal close-packed micro-nano structure periodic array on the output end surface of the above quartz substrate, with the top of the cone facing the inside of the quartz (such as Figure 5 , Fig. 6A The operating parameters of the electron beam direct writing technology are as follows: the working vacuum degree is 5×10 -4 Pa, the maximum acceleration voltage is 150kV, the scanning main frequency is 12MHz, the scanning step is 2nm, and the minimum beam spot is 3nm. The conical micro-nano structure periodic array includes a plurality of conical micro-nano structure units, and the etched period P is 300nm, the duty cycle is 1, the depth / height of the structure unit is 220nm, and the radius of the circumscribed circle of the bottom projection is 150nm.

[0115] After S3 etching is completed, the samples are cleaned with acetone, anhydrous ethanol, and deionized water ultrasonically (power is 80kHz) for 5 minutes each, and the ultrasonic cleaning is repeated 3 times (to clean the organic pollution, grease, and dust pollution caused by the sample during the circulation and operation process);

[0116] S4 was then cleaned with 0.01 vol% dilute hydrofluoric acid, 0.1 wt% sodium hydroxide solution, and anhydrous ethanol, each with ultrasound (power of 80 kHz) for 1 minute, and repeated ultrasound for 3 times (chemical corrosion method of alternating acid and alkali erosion to assist in further improving the etching morphology), and finally a periodic array of micro-nano structures with neatly edged conical hollow bodies was obtained.

[0117] S5 uses atomic layer deposition (ALD) technology to plate a magnesium oxide film on the surface of the above-mentioned output end face as the filling material of the conical hollow body micro-nano structure, and uses bis(cyclopentadienyl)magnesium (Mg(C 5 H 5 ) 2 ) as a precursor, H 2 O as reactant, N 2 With N 2 O 4 as carrier gas, reaction temperature of 200° C. and growth rate of 0.1 nm / cycle, a magnesium oxide film with a thickness of 270 nm and a refractive index of 1.8@250 nm was grown.

[0118] S6 uses chemical mechanical polishing technology to polish the surface of the output end face after the above coating, and the process parameters used are a speed of 70rpm and a pressure of 6g / mm 2 The polishing liquid flow rate is 2 mL / min, and the excess magnesium oxide film layer is polished to obtain a periodic array micro-nanostructure functional layer 2 of embedded conical solid bodies filled with magnesium oxide with a thickness of 220 nm, such as Figure 2 As shown, the micro-nano structure periodic array functional layer 2 includes a plurality of micro-nano structure units 3; the micro-nano structure units 3 are filled with magnesium oxide to form a solid micro-nano structure periodic array.

[0119] After S7 polishing is completed, the sample is cleaned with acetone, anhydrous ethanol, and deionized water ultrasonically (power is 45kHz) for 5 minutes each, and the cleaning is repeated 3 times (cleaning removes organic matter, dust, particles and other contaminations that the sample is exposed to during the circulation and operation process), and a surface micro-nanostructure transmission quartz optical element with a periodic array of conical micro-nanostructures filled with magnesium oxide thin film materials at the output end is obtained; wherein the radius of the circumscribed circle of the bottom of the cone is 150nm, the period P is 300nm, and the height / depth is 220nm.

[0120] The surface micro-nanostructured transmission quartz optical element is used as an optical window to make a cesium telluride photocathode. Compared with conventional quartz optical windows (such as Figure 3 As shown, it includes substrate 1a), its interface reflectivity @250nm is reduced by 73%, transmittance @250nm is increased by 3.33%, and quantum efficiency is increased by 30.6%, see Table 1.

[0121] Embodiment 6:

[0122] S1 uses a quartz substrate (n=1.5@250nm) of Φ18*3mm as a transparent substrate, and is cleaned by ultrasonic cleaning (power of 45kHz) of acetone, anhydrous ethanol, and deionized water for 5 minutes each, and the cleaning is repeated 3 times to obtain a clean quartz substrate for use.

[0123] S2 uses electron beam direct writing (EBL) technology to etch a conical hollow body hexagonal close-packed micro-nano structure periodic array on the output end surface of the above quartz substrate, with the top of the cone facing the inside of the quartz (such as Figure 5 , Fig. 6A The operating parameters of the electron beam direct writing technology are as follows: the working vacuum degree is 5×10 -4 Pa, the maximum acceleration voltage is 150kV, the scanning main frequency is 12MHz, the scanning step is 2nm, and the minimum beam spot is 3nm. The conical micro-nano structure periodic array includes a plurality of conical micro-nano structure units, and the etched period P is 100nm, the duty cycle is 1, the depth / height of the structure unit is 80nm, and the radius of the circumscribed circle of the bottom projection is 50nm.

[0124] After S3 etching is completed, the samples are cleaned with acetone, anhydrous ethanol, and deionized water ultrasonically (power is 80kHz) for 5 minutes each, and the ultrasonic cleaning is repeated 3 times (to clean the organic pollution, grease, and dust pollution caused by the sample during the circulation and operation process);

[0125] S4 was then cleaned with 0.01 vol% dilute hydrofluoric acid, 0.1 wt% sodium hydroxide solution, and anhydrous ethanol, each with ultrasound (power of 80 kHz) for 1 minute, and repeated ultrasound for 3 times (chemical corrosion method of alternating acid and alkali erosion to assist in further improving the etching morphology), and finally a periodic array of micro-nano structures with neatly edged conical hollow bodies was obtained.

[0126] S5 uses atomic layer deposition (ALD) technology to plate a magnesium oxide film on the surface of the above-mentioned output end face as the filling material of the conical hollow body micro-nano structure, and uses bis(cyclopentadienyl)magnesium (Mg(C 5 H 5 ) 2 ) as a precursor, H 2 O as reactant, N 2 With N 2 O 4 as carrier gas, reaction temperature of 200° C. and growth rate of 0.1 nm / cycle, a magnesium oxide film with a thickness of 150 nm and a refractive index of 1.8@250 nm was grown.

[0127] S6 uses chemical mechanical polishing technology to polish the surface of the output end face after the above coating, and the process parameters used are a speed of 70rpm and a pressure of 6g / mm 2 The polishing liquid flow rate is 2 mL / min, and the excess magnesium oxide film layer is polished to obtain a periodic array micro-nano structure functional layer 2 of embedded conical solid bodies filled with magnesium oxide with a thickness of 70 nm, such as Figure 2As shown, the micro-nano structure periodic array functional layer 2 includes a plurality of micro-nano structure units 3; the micro-nano structure units 3 are filled with magnesium oxide to form a solid micro-nano structure periodic array.

[0128] After S7 polishing is completed, the sample is cleaned with acetone, anhydrous ethanol, and deionized water ultrasonically (power is 45kHz) for 5 minutes each, and the cleaning is repeated 3 times (cleaning removes organic matter, dust, particles and other contaminations that the sample is exposed to during the circulation and operation process), and a surface micro-nanostructure transmission quartz optical element with a periodic array of conical micro-nanostructures filled with magnesium oxide thin film materials at the output end is obtained; wherein the radius of the circumscribed circle of the bottom of the cone is 50nm, the period P is 100nm, and the height / depth is 80nm.

[0129] The surface micro-nanostructured transmission quartz optical element is used as an optical window to make a cesium telluride photocathode. Compared with conventional quartz optical windows (such as Figure 3 As shown, it includes substrate 1a), its interface reflectivity @250nm is reduced by 67%, transmittance @250nm is increased by 3.78%, and quantum efficiency is increased by 32.2%, see Table 1.

[0130] Embodiment 7:

[0131] S1 uses a quartz substrate of Φ25*4mm (refractive index n=1.5@250nm) as a transparent substrate, and is cleaned by ultrasonic cleaning (power of 45kHz) with acetone, anhydrous ethanol, and deionized water for 5 minutes each, and the cleaning is repeated 3 times to obtain a clean quartz substrate for use.

[0132] S2 uses inductively coupled plasma etching technology (ICP) to etch the surface of the quartz output end to produce a cylindrical hollow body hexagonal close-packed micro-nano structure periodic array (such as Figure 5 , Fig.9A The etching process specifically includes: coating 300nm photoresist on the end surface by uniform coating, exposing and developing to obtain a hexagonal close-packed circular hole structure array pattern with a circle radius of 50nm and a period P of 160nm, and then etching to obtain a quartz substrate pattern of a hexagonal close-packed circular hole structure array. The ICP etching parameters are set as follows: the pre-vacuum degree is 1×10 -4 Pa, Ar was introduced as sputtering gas with a flow rate of 60 sccm, and CF 4 Using 20 sccm as the reaction gas, a flow rate of 20 sccm, a vacuum degree in the chamber of 2 Pa, an input power of 700 W, and a bias power of 300 W, an array of circular hole hollow bodies with a depth / height of 110 nm, a circular hole radius of 50 nm, a period P of 160 nm, and a duty cycle of 0.625 was obtained.

[0133] After S3 etching is completed, the samples are ultrasonically cleaned (with a power of 80kHz) with acetone, anhydrous ethanol, and deionized water for 5 minutes each, and the ultrasonic cleaning is repeated 3 times (to clean the organic contamination, grease, and dust contamination that the samples have been exposed to during circulation and operation).

[0134] S4 was then cleaned with 0.01 vol% dilute hydrofluoric acid, 0.1 wt% sodium hydroxide solution, and anhydrous ethanol, each with ultrasound (power of 80 kHz) for 1 minute, and repeated ultrasound for 3 times (chemical corrosion method of alternating acid and alkali erosion to assist in further improving the etching morphology), and finally a periodic array of micro-nano structures with neatly edged conical hollow bodies was obtained.

[0135] S5 uses atomic layer deposition (ALD) technology to plate a magnesium oxide film on the surface of the above-mentioned output end face as the filling material of the conical hollow body micro-nano structure, and uses bis(cyclopentadienyl)magnesium (Mg(C 5 H 5 ) 2 ) as a precursor, H 2 O as reactant, N 2 With N 2 O 4 as carrier gas, reaction temperature of 200° C. and growth rate of 0.1 nm / cycle, a magnesium oxide film with a thickness of 160 nm and a refractive index of 1.8@250 nm was grown.

[0136] S6 uses chemical mechanical polishing technology to polish the surface of the output end face after the above coating, and the process parameters used are a speed of 70rpm and a pressure of 6g / mm 2 The polishing liquid flow rate is 2 mL / min, and the excess magnesium oxide film layer is polished to obtain a periodic array micro-nano structure functional layer 2 of embedded cylindrical solid bodies filled with magnesium oxide with a thickness of 110 nm, such as Figure 2 As shown, the micro-nano structure periodic array functional layer 2 includes a plurality of micro-nano structure units 3; the micro-nano structure units 3 are filled with magnesium oxide to form a solid micro-nano structure periodic array.

[0137] After S7 polishing, the sample was cleaned with acetone, anhydrous ethanol, and deionized water ultrasonically (power of 45kHz) for 5 minutes each, and the cleaning was repeated 3 times (cleaning to remove organic matter, dust, particles and other contaminations on the sample during the circulation and operation process), and a surface micro-nanostructure transmission quartz optical element with a periodic array of cylindrical micro-nanostructures filled with magnesium oxide thin film material at the output end was obtained; wherein the radius of the bottom circumscribed circle of the cylinder is 50nm, the period P is 160nm, and the height / depth is 110nm.

[0138] The surface micro-nanostructured transmission quartz optical element is used as an optical window to make a cesium telluride photocathode. Compared with conventional quartz optical windows (such as Figure 3As shown, it includes a substrate 1a), whose interface reflectivity @250nm is reduced by 50%, the transmittance @250nm is increased by 2.78%, and the quantum efficiency is increased by 27.8%, see Table 1.

[0139] Embodiment 8:

[0140] S1 uses a quartz substrate (n=1.5@250nm) of Φ18*3mm as a transparent substrate, and is cleaned by ultrasonic cleaning (power of 45kHz) of acetone, anhydrous ethanol, and deionized water for 5 minutes each, and the cleaning is repeated 3 times to obtain a clean quartz substrate for use.

[0141] S2 uses inductively coupled plasma etching technology (ICP) to etch a periodic array of hexagonal close-packed micro-nano structures with a flat-top Gaussian surface on the surface of the quartz output end, with the top of the flat-top Gaussian surface facing the inside of the substrate (such as Figure 5 , Figure 8C The etching process specifically includes: coating 300nm photoresist on the end surface by uniform coating, exposing and developing to obtain a hexagonal close-packed structure array pattern with a circumscribed circle radius of 50nm and a period P of 160nm, and then etching to obtain a quartz substrate pattern of a hexagonal close-packed structure array. The ICP etching parameters are set as follows: the pre-vacuum degree is 1×10 - 4 Pa, Ar was introduced as sputtering gas with a flow rate of 60 sccm, and CF 4 Using 20 sccm as the reaction gas, a flow rate of 20 sccm, a vacuum degree in the chamber of 2 Pa, an input power of 700 W, and a bias power of 300 W, an array of flat-topped Gaussian hollow bodies with a depth / height of 110 nm, a bottom circumscribed circle radius of 50 nm, a top circumscribed circle radius of 20 nm, a period P of 160 nm, and a duty cycle of 0.625 was obtained.

[0142] S3: Soak the quartz substrate with the surface micro-nano structure in a mixture of concentrated sulfuric acid and 20 vol% hydrogen peroxide for 30 minutes, and then clean it with deionized water and anhydrous ethanol by ultrasonic cleaning (power of 80 kHz) for 5 minutes each. Repeat the ultrasonic cleaning three times to remove the glue mold, and obtain a quartz substrate with a clean surface and micro-nano structure.

[0143] S4 was then cleaned by 0.01 vol% dilute hydrofluoric acid solution, 0.1 wt% sodium hydroxide solution, and anhydrous ethanol, each with ultrasonic cleaning (power of 80 kHz) for 1 minute, and repeated ultrasonic cleaning 3 times (a chemical corrosion method of alternating acid and alkali corrosion, to further improve the etching morphology, and finally obtain a flat-top Gaussian hollow body morphology array with neat edges.

[0144] S5 uses atomic layer deposition (ALD) technology to plate a magnesium oxide film on the surface of the above-mentioned output end face as the filling material of the flat-top Gaussian hollow body micro-nano structure, and uses bis(cyclopentadienyl)magnesium (Mg(C 5 H 5 ) 2 ) as a precursor, H 2 O as reactant, N 2 With N 2 O 4 as carrier gas, reaction temperature of 200° C. and growth rate of 0.1 nm / cycle, a magnesium oxide film with a thickness of 160 nm and a refractive index of 1.8@250 nm was grown.

[0145] S6 uses chemical mechanical polishing technology to polish the surface of the output end face after the above coating, and the process parameters used are a speed of 70rpm and a pressure of 6g / mm 2 The polishing liquid flow rate is 2 mL / min, and the excess magnesium oxide film layer is polished to obtain a periodic array micro-nanostructure functional layer 2 of embedded flat-top Gaussian solid bodies filled with magnesium oxide with a thickness of 110 nm, such as Figure 2 As shown, the micro-nano structure periodic array functional layer 2 includes a plurality of micro-nano structure units 3; the micro-nano structure units 3 are filled with magnesium oxide to form a solid micro-nano structure periodic array.

[0146] After S7 polishing is completed, the sample is cleaned with acetone, anhydrous ethanol, and deionized water ultrasonically (power is 45kHz) for 5 minutes each, and the cleaning is repeated 3 times (cleaning removes organic matter, dust, particles and other contaminants that the sample is exposed to during the circulation and operation process), and a surface micro-nanostructure transmission quartz optical element with a periodic array of conical micro-nanostructures filled with magnesium oxide thin film materials at the output end is obtained; wherein the bottom circumscribed circle radius of the flat-top Gaussian surface is 50nm, the top circumscribed circle radius is 20nm, the period P is 160nm, and the height / depth is 110nm, such as Figure 8C shown.

[0147] The surface micro-nanostructured transmission quartz optical element is used as an optical window to make a cesium telluride photocathode. Compared with conventional quartz optical windows (such as Figure 3 As shown, it includes substrate 1a), its interface reflectivity @250nm is reduced by 57%, transmittance @250nm is increased by 3.22%, and quantum efficiency is increased by 45%, see Table 1.

[0148] Embodiment 9:

[0149] S1 uses a quartz substrate (n=1.5@250nm) of Φ25*4mm as a transparent substrate, and is cleaned by ultrasonic cleaning (power of 45kHz) of acetone, anhydrous ethanol, and deionized water for 5 minutes each, and the cleaning is repeated 3 times to obtain a clean quartz substrate for use.

[0150] S2 uses ion beam etching (IBE) technology to etch a periodic array of square-shaped hollow bodies with close-packed micro-nano structures on the surface of the output end of the quartz substrate, with the top of the square-shaped hollow body facing the inside of the quartz (such as Figure 4 , Figure 7B The etching process specifically includes: coating 300nm photoresist on the end surface by uniform coating, exposing and developing to obtain a tetragonal close-packed square hole structure array pattern with a circumscribed circle radius of 50nm and a period P of 160nm; the parameters of reactive ion beam etching are set as follows: the pre-vacuum degree is 1×10 -3 Pa, Ar / O 2 Mixed gas (volume ratio is Ar:O 2 =4:1) as the sputtering gas, flow rate 80sccm, chamber vacuum degree 3Pa, ion beam energy 320eV, beam current density 0.5mA / cm 2 , a square-cone-shaped hollow body array with a bottom circumscribed circle radius of 50 nm, a top circumscribed circle radius of 20 nm, a period P of 160 nm, a depth / height of 110 nm, and a duty cycle of 0.625 was obtained by etching.

[0151] S3: Soak the quartz substrate with the surface micro-nano structure in a mixture of concentrated sulfuric acid and 20 vol% hydrogen peroxide for 30 minutes, and then clean it with deionized water and anhydrous ethanol by ultrasonic cleaning (power of 80 kHz) for 5 minutes each. Repeat the ultrasonic cleaning three times to remove the glue mold, and obtain a quartz substrate with a clean surface and micro-nano structure.

[0152] S4: The quartz substrate with the cleaned surface of the micro-nano structure is cleaned by ultrasonic cleaning (power of 80kHz) for 1 minute in a 0.2vol% dilute hydrofluoric acid solution, a 2wt% sodium hydroxide solution, and anhydrous ethanol, and the ultrasonic cleaning is repeated 3 times (a chemical corrosion method of alternating acid and alkali erosion to further improve the etching morphology, and finally a square platform morphology with neat edges is obtained.

[0153] S5 uses atomic layer deposition (ALD) technology to plate a magnesium oxide film on the surface of the above-mentioned output end face as the filling material of the flat-top Gaussian hollow body micro-nano structure, and uses bis(cyclopentadienyl)magnesium (Mg(C 5 H 5 ) 2 ) as a precursor, H 2 O as reactant, N 2 With N 2 O 4 as carrier gas, reaction temperature of 200° C. and growth rate of 0.1 nm / cycle, a magnesium oxide film with a thickness of 160 nm and a refractive index of 1.8@250 nm was grown.

[0154] S6 uses chemical mechanical polishing technology to polish the surface of the output end face after the above coating, and the process parameters used are a speed of 70rpm and a pressure of 6g / mm2 The polishing liquid flow rate is 2 mL / min, and the excess magnesium oxide film layer is polished to obtain a periodic array micro-nanostructure functional layer 2 of embedded flat-top Gaussian solid bodies filled with magnesium oxide with a thickness of 110 nm, such as Figure 2 As shown, the micro-nano structure periodic array functional layer 2 includes a plurality of micro-nano structure units 3; the micro-nano structure units 3 are filled with magnesium oxide to form a solid micro-nano structure periodic array.

[0155] After S7 polishing, the sample was cleaned with acetone, anhydrous ethanol, and deionized water ultrasonically (power of 45kHz) for 5 minutes each, and the cleaning was repeated 3 times (cleaning to remove organic matter, dust, particles and other contaminants that the sample was exposed to during the circulation and operation process), and a surface micro-nanostructure transmission quartz optical element with a periodic array of square-cone-shaped micro-nanostructures filled with magnesium oxide thin film material at the output end was obtained; wherein the bottom circumscribed circle radius of the square-cone shape is 50nm, the top circumscribed circle radius is 20nm, the period P is 160nm, and the height / depth is 110nm.

[0156] The surface micro-nanostructured transmission quartz optical element is used as an optical window to make a cesium telluride photocathode. Compared with conventional quartz optical windows (such as Figure 3 As shown, it includes substrate 1a), its reflectivity @250nm is reduced by 45%, the transmittance @250nm is increased by 1.89%, and the quantum efficiency is increased by 35%, see Table 1.

[0157] Embodiment 10:

[0158] S1 uses a quartz substrate of Ф18*3mm (refractive index n=1.5@250nm) as a transparent substrate, and is cleaned by acetone, anhydrous ethanol, and deionized water ultrasonically (power is 45kHz) for 5 minutes each, and the cleaning is repeated 3 times to obtain a clean quartz substrate for use.

[0159] S2 uses electron beam direct writing (EBL) technology to etch a conical hollow body hexagonal close-packed micro-nano structure periodic array on the output end surface of the above quartz substrate, with the top of the cone facing the inside of the quartz (such as Figure 5 , Fig. 6A The operating parameters of the electron beam direct writing technology are as follows: the working vacuum degree is 5×10 -4 Pa, the maximum acceleration voltage is 100kV, the scanning main frequency is 12MHz, the scanning step is 2nm, and the minimum beam spot is 3nm. The conical micro-nano structure periodic array includes a plurality of conical micro-nano structure units, and the etched period P is 160nm, the duty cycle is 1, the depth / height of the structure unit is 110nm, and the radius of the circumscribed circle of the bottom projection is 80nm.

[0160] After S3 etching is completed, ultrasonic cleaning (power is 80kHz) is performed in acetone, anhydrous ethanol, and deionized water for 5 minutes respectively, and ultrasonic cleaning is repeated 3 times (to clean the organic pollution, grease, and dust pollution that the sample has been exposed to during the circulation and operation process).

[0161] S4 was then cleaned with 0.01 vol% dilute hydrofluoric acid, 0.1 wt% sodium hydroxide solution, and anhydrous ethanol, each with ultrasound (power of 80 kHz) for 1 minute, and repeated ultrasound for 3 times (chemical corrosion method of alternating acid and alkali erosion to assist in further improving the etching morphology), and finally a periodic array of micro-nano structures with neatly edged conical hollow bodies was obtained.

[0162] S5 uses atomic layer deposition (ALD) technology to plate a hafnium oxide film on the surface of the above-mentioned output end face as the filling material of the conical hollow micro-nano structure, and uses tetradiethylamino hafnium as a precursor, H 2 O as reactant, N 2 As the carrier gas, the reaction temperature is 250° C., the hafnium oxide growth rate is 0.1 nm / cycle, and a hafnium oxide film layer with a thickness of 160 nm and a refractive index of 2.12@250 nm is grown.

[0163] S6 uses chemical mechanical polishing technology to polish the surface of the output end face after the above coating, and the process parameters used are a speed of 90rpm and a pressure of 8g / mm 2 The polishing liquid flow rate is 3 mL / min, and the excess hafnium oxide film layer is polished away to obtain a periodic array micro-nanostructure functional layer 2 of embedded conical solid bodies filled with hafnium oxide with a thickness of 110 nm, such as Figure 2 As shown, the micro-nano structure periodic array functional layer 2 includes a plurality of micro-nano structure units 3; the micro-nano structure units 3 are filled with hafnium oxide to form a solid micro-nano structure periodic array.

[0164] After S7 polishing, the sample was cleaned with acetone, anhydrous ethanol, and deionized water ultrasonically (power of 45kHz) for 5 minutes each, and the cleaning was repeated 3 times (cleaning to remove organic matter, dust, particles and other contaminants that the sample was exposed to during the circulation and operation process), and a surface micro-nanostructure transmission quartz optical element with a periodic array of conical micro-nanostructures filled with hafnium oxide thin film material at the output end was obtained; wherein the radius of the circumscribed circle of the bottom of the cone is 80nm, the period P is 160nm, and the height / depth is 110nm.

[0165] The surface micro-nanostructured transmission quartz optical element is used as an optical window to make a cesium telluride photocathode. Compared with conventional quartz optical windows (such as Figure 3As shown, it includes substrate 1a), its interface reflectivity @250nm is reduced by 81%, transmittance @250nm is increased by 5.89%, and quantum efficiency is increased by 72.2%, see Table 1.

[0166] Embodiment 11:

[0167] S1 uses a quartz substrate of Ф18*3mm (refractive index n=1.5@250nm) as a transparent substrate, and is cleaned by acetone, anhydrous ethanol, and deionized water ultrasonically (power is 45kHz) for 5 minutes each, and the cleaning is repeated 3 times to obtain a clean quartz substrate for use.

[0168] S2 uses electron beam direct writing (EBL) technology to etch a conical hollow body hexagonal close-packed micro-nano structure periodic array on the output end surface of the above quartz substrate, with the top of the cone facing the inside of the quartz (such as Figure 5 , Fig. 6A The operating parameters of the electron beam direct writing technology are as follows: the working vacuum degree is 5×10 -4 Pa, the maximum acceleration voltage is 100kV, the scanning main frequency is 12MHz, the scanning step is 2nm, and the minimum beam spot is 3nm. The conical micro-nano structure periodic array includes a plurality of conical micro-nano structure units, and the etched period P is 160nm, the duty cycle is 1, the depth / height of the structure unit is 110nm, and the radius of the circumscribed circle of the bottom projection is 80nm.

[0169] After S3 etching is completed, ultrasonic cleaning (power is 80kHz) is performed in acetone, anhydrous ethanol, and deionized water for 5 minutes respectively, and ultrasonic cleaning is repeated 3 times (to clean the organic pollution, grease, and dust pollution that the sample has been exposed to during the circulation and operation process).

[0170] S4 was then cleaned with 0.01 vol% dilute hydrofluoric acid, 0.1 wt% sodium hydroxide solution, and anhydrous ethanol, each with ultrasound (power of 80 kHz) for 1 minute, and repeated ultrasound for 3 times (chemical corrosion method of alternating acid and alkali erosion to assist in further improving the etching morphology), and finally a periodic array of micro-nano structures with neatly edged conical hollow bodies was obtained.

[0171] S5 uses atomic layer deposition (ALD) technology to plate a zirconium oxide / aluminum oxide composite film on the output end face of the above glass, using tetrakis dimethylamino zirconium and trimethylaluminum as precursors, H 2 O as reactant, N 2Using 2-nitrogen-2-nitrogen as carrier gas and reaction temperature of 90°C, the growth rate of zirconium oxide is 0.1 nm / cycle and the growth rate of aluminum oxide is 0.05 nm / cycle, a zirconium oxide / aluminum oxide composite film layer with a thickness of 160 nm and a refractive index of 2.0 (zirconia:aluminum oxide = 1:5 (thickness ratio)) is grown.

[0172] S6 uses chemical mechanical polishing technology to polish the surface of the output end face after the above coating, and the process parameters used are a speed of 100rpm and a pressure of 8g / mm 2 The polishing liquid flow rate is 3 mL / min, and the excess zirconium oxide / aluminum oxide composite film layer is polished to obtain a periodic array micro-nano structure functional layer 2 with a thickness of 110 nm and embedded conical solid bodies filled with zirconium oxide / aluminum oxide composite film layers, such as Figure 2 As shown, the micro-nano structure periodic array functional layer 2 includes a plurality of micro-nano structure units 3; the micro-nano structure units 3 are filled with a zirconium oxide / aluminum oxide composite film layer to form a solid micro-nano structure periodic array.

[0173] After S7 polishing, the sample was cleaned with acetone, anhydrous ethanol, and deionized water ultrasonically (power of 45kHz) for 5 minutes each, and the cleaning was repeated 3 times (cleaning to remove organic matter, dust, particles and other contaminants that the sample was exposed to during circulation and operation), and a surface micro-nanostructure transmission type quartz optical element with a periodic array of a conical micro-nanostructure filled with zirconium oxide / aluminum oxide composite thin film material at the output end was obtained. The radius of the bottom circumscribed circle of the cone is 80nm, the period P is 160nm, and the height / depth is 110nm.

[0174] The surface micro-nanostructured transmission quartz optical element is used as an optical window to make a cesium telluride photocathode. Compared with conventional quartz optical windows (such as Figure 3 As shown, it includes a substrate 1a), whose interface reflectivity @250nm is reduced by 80%, the transmittance @250nm is increased by 5.78%, and the quantum efficiency is increased by 61.7%, see Table 1.

[0175] The performance data of the quartz light windows with micro-nano structure functional layers obtained in Examples 1-11 and Comparative Examples 1-2 and conventional quartz light windows are summarized in Table 1. The quartz light windows with micro-nano structure functional layers obtained in Examples 1-11 and Comparative Examples 1-2 and conventional quartz light windows were used as optical windows to test the transmittance of their exit end faces; a quartz light window with a cesium telluride photocathode was formed by evaporating a cesium telluride photocathode film layer of the same specification, and the interface reflectivity and quantum efficiency were tested under the same conditions.

[0176] The transmittance is measured by using an ultraviolet spectrometer to measure the transmittance of the quartz window under 250nm incident light;

[0177] The interface reflectivity is measured by ultraviolet spectrometer at the interface of the output end of the quartz window with cesium telluride photocathode under 250nm incident light;

[0178] The quantum efficiency is measured by a quantum efficiency meter to measure the number of photogenerated electrons corresponding to a 250nm photon passing through a quartz window and irradiating the cesium telluride photocathode.

[0179] Table 1

[0180]

[0181] From the data in Table 1, it can be seen that the quartz light window with a micro-nanostructure functional layer obtained in Examples 1-11 of the present invention has a transmittance of 91.7%-95.3% at a working wavelength of 250nm, an interface reflectivity of 1.9%-5.5%, and a quantum efficiency of 23.00%-31.00%.

[0182] By comparing Example 1, Example 2 and Example 3, it can be seen that when other parameters are fixed and only the depth / height of the micro-nano structure is changed within the range of 80nm-300nm, as the depth / height of the micro-nano structure gradually increases, the reflectivity of the output end interface shows a downward trend, and the transmittance of the light window shows an increasing trend, but the corresponding cesium telluride photocathode quantum efficiency shows a trend of first increasing and then decreasing, indicating that the quantum efficiency does not entirely depend on the size of the transmittance, but also depends on the size optimization of the structural unit of the periodic array of the micro-nano structure. According to experimental verification, when the depth / height of the micro-nano structure is 0.5-2 times the period P, the corresponding diffraction utilization efficiency is generally higher; generally, the greater the depth / height of the micro-nano structure, the better the corresponding refractive index gradient effect, and the smaller the reflection of the micro-nano structure functional layer.

[0183] By comparing Example 1 and Example 4, it can be seen that when other parameters are fixed unchanged, only the duty cycle of the periodic array of micro-nano structures is changed. The larger the duty cycle, the higher the corresponding transmittance, the smaller the interface reflectivity, and the higher the quantum efficiency. Since the micro-nano structure is an embedded high-refractive index solid micro-nano structure, the larger the duty cycle, the larger the refractive index gradient value of the corresponding output end interface, and the smaller the deviation from the large refractive index of the cesium telluride photocathode. This indicates that the smaller the refractive index deviation of the output end face, the higher the day-blind ultraviolet transmittance, the more day-blind ultraviolet photons participate in photoelectric conversion, and the greater the corresponding quantum efficiency.

[0184] By comparing Example 4, Comparative Example 1 and Comparative Example 2, it can be seen that the period of the micro-nano structure array has a significant effect on the quantum efficiency of the cesium telluride photocathode. According to the verification, the period P of the micro-nano structure corresponding to the day-blind ultraviolet is more suitable in the range of 100nm-300nm. When the period P is higher than 300nm, on the one hand, multiple diffraction occurs, the diffraction efficiency decreases, and the quantum efficiency decreases; on the other hand, different periods P are applicable to different working bands. When the period P is higher than 300nm, such as 600nm, it is suitable for the near-infrared band. If it is used in the day-blind ultraviolet band, it will cause the day-blind ultraviolet reflection to remain high, limiting the improvement of quantum efficiency, and cannot meet the needs of high-performance day-blind ultraviolet detection equipment. When the period P is lower than 100nm, such as 60nm, the diffraction wave of the transmitted light of the day-blind ultraviolet part is obviously evanescent, resulting in a decrease in the effect of increasing the photon optical path caused by diffraction, and a decrease in quantum efficiency, which cannot meet the needs of high-performance day-blind ultraviolet detection equipment.

[0185] By comparing Example 4, Example 5 and Example 6, it can be seen that when the duty cycle is the same and the utilization efficiency of the transmitted diffraction light corresponding to the structure depth / height is higher, for the day-blind ultraviolet quantum efficiency, there is an optimal value for the micro-nano structure period P, which is between 120nm-180nm.

[0186] By comparing Example 1, Example 7, Example 8 and Example 9, it can be seen that when the period, duty cycle and depth / height of the micro-nano structure array remain unchanged, the quantum efficiency corresponding to different structural morphologies is also different. By comparison, it can be seen that the quantum efficiency corresponding to the conical morphology and the flat-top Gaussian morphology is higher, while the quantum efficiency corresponding to the cylindrical morphology and the square table morphology is lower. The conical morphology and the flat-top Gaussian morphology are gradual morphologies, which construct a micro-nano structure functional layer with a gradual refractive index, thereby reducing the interface reflectivity and enhancing the transmittance, thereby increasing the number of day-blind ultraviolet photons participating in the photoelectric conversion of the cesium telluride photocathode, and therefore, the quantum efficiency is higher. The cylindrical morphology is not a gradual morphology, and only plays the role of buffering the refractive index deviation. Therefore, the effect of reducing the interface reflectivity and increasing the transmittance is limited, resulting in a lower quantum efficiency. Although the square terrace morphology is a gradual morphology, the square cross-sectional area is smaller than the area of ​​its circumscribed circle, that is, the equivalent refractive index corresponding to the square terrace morphology is lower than the area of ​​other circular cross-sections such as cones and flat-top Gaussian shapes with the same bottom circumscribed circle. Therefore, the gradient refractive index value of the square terrace morphology is small, resulting in a large refractive index deviation between the square terrace morphology and the cesium telluride photocathode. Therefore, the quantum efficiency corresponding to the square terrace morphology is low.

[0187] By comparing Example 4, Example 10 and Example 11, it can be seen that when the period, duty cycle and depth / height of the micro-nano structure array remain unchanged, the quantum efficiencies corresponding to different filling film materials are also different. By comparison, it can be seen that the greater the refractive index of the filling material, the greater the quantum efficiency tends to be. This is because when the micro-nano structure morphology and size are the same, the greater the refractive index of the filling film material, the greater the refractive index of the corresponding solid micro-nano structure, and the smaller the refractive index deviation between the cesium telluride photocathode, which is reflected in the reduction of interface reflectivity and increase of transmittance, the increase of day-blind ultraviolet photons entering the cesium telluride photocathode film layer to participate in photoelectric conversion, and the increase of quantum efficiency.

[0188] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0189] The microstructure described in the present invention, any simple deposition of a film layer on the surface of the microstructure to modify, protect or passivate the surface of the microstructure should be within the protection scope of the present invention.

[0190] The numerical range described in the present invention includes all the numerical values ​​within the range, and includes the range value formed by any two numerical values ​​within the range. Different numerical values ​​of the same indicator appearing in all embodiments of the present invention can be arbitrarily combined to form a range value.

[0191] The technical features in the claims and / or the specification of the present invention may be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also within the protection scope of the present invention.

[0192] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a quartz window for enhanced solar-blind ultraviolet detection, characterized in that: The following steps are involved: 1) etching a periodic array of hollow micro-nano structures with gradual morphology on the exit end face of a clean quartz substrate with high transmittance in the solar-blind ultraviolet band, and obtaining a clean quartz element with a periodic array of hollow micro-nano structures with neat edges after multiple ultrasonic cleaning; 2) coating the output end surface of the quartz element obtained in step 1) with a solar-blind ultraviolet high-transmittance thin film material as a filling material for the hollow body structure; 3) The output end face after coating in step 2) is polished to obtain a micro-nano structure periodic array functional layer with an embedded solid body morphology with a thickness of 80nm to 300nm, and then ultrasonically cleaned to obtain a quartz light window for day-blind ultraviolet detection enhancement with a micro-nano structure periodic array.

2. The method for preparing the quartz window for enhanced solar-blind ultraviolet detection according to claim 1, characterized in that: In step 1), the refractive index of the quartz substrate at a wavelength of 250nm is n=1.5, and the transmittance at a wavelength of 250nm is ≥90%; the periodic array of hollow micro-nano structures is distributed in a hexagonal close-packed or tetragonal close-packed manner; the top of the periodic array of hollow micro-nano structures faces the inside of the quartz substrate.

3. The method for preparing the quartz window for enhanced solar-blind ultraviolet detection according to claim 1, characterized in that: In step 1), the periodic array of hollow micro-nano structures with a gradual morphology includes a plurality of micro-nano structure units, the morphology of the micro-nano structure units is conical, trapezoidal, Gaussian or cylindrical, the bottom projection contour of the micro-nano structure unit is circular, square or regular polygonal, the bottom projection circle radius / circumscribed circle radius is 50nm to 150nm, the top projection circle radius / circumscribed circle radius is less than or equal to 50nm, the period is 100nm to 300nm, the height / depth is 80nm to 300nm, and the duty cycle of the periodic array of micro-nano structures is greater than or equal to 0.

5.

4. The method for preparing a quartz window for enhanced solar-blind ultraviolet detection according to claim 1, characterized in that: In step 1), the ultrasonic cleaning includes conventional ultrasonic cleaning, acid-base alternating ultrasonic cleaning and anhydrous ethanol / isopropanol ultrasonic cleaning.

5. The method for preparing the quartz window for enhanced solar-blind ultraviolet detection according to claim 1, characterized in that: In step 2), the refractive index of the film material is greater than that of the transparent substrate and is transparent to ultraviolet light at a working wavelength of 200nm to 280nm; the film material is selected from a film of magnesium oxide, hafnium oxide, aluminum oxide and zirconium oxide or a composite film of at least two materials.

6. A quartz window for enhanced solar-blind ultraviolet detection, characterized in that: The quartz light window for enhanced solar-blind ultraviolet detection comprises a quartz substrate, wherein the quartz substrate has an incident end face for receiving and transmitting incident light and an opposite exit end face, wherein the exit end face of the quartz substrate has a hollow micro-nano structure periodic array with a gradually changing morphology, wherein the micro-nano structure periodic array comprises a plurality of micro-nano structure units; the micro-nano structure units of the exit end face are filled with a transparent thin film material with a high refractive index to form a solid micro-nano structure periodic array.

7. The quartz window for enhanced solar-blind ultraviolet detection according to claim 6, characterized in that: The morphology of the hollow body micro-nano structure periodic array is conical, trapezoidal, Gaussian or cylindrical, and its bottom projection contour on the plane is circular, square or regular polygonal, the bottom projection circle radius / circumscribed circle radius R is 50nm to 150nm, the top projection circle radius / circumscribed circle radius r≤50nm, the period P is 100nm to 300nm, the height / depth H is 80nm to 300nm, and the duty cycle of the micro-nano structure periodic array is ≥0.

5.

8. The quartz window for enhanced solar-blind ultraviolet detection according to claim 6, characterized in that: The substrate is made of quartz optical quartz with a refractive index of 1.5 and a transmittance of ≥90% in the effective range of 200nm to 280nm. The transparent film material has a refractive index greater than that of the quartz substrate and is transparent to ultraviolet light with a working wavelength of 200nm to 280nm.

9. An optical device, characterized in that: It includes a quartz light window for day-blind ultraviolet detection enhancement; the quartz light window for day-blind ultraviolet detection enhancement includes a quartz substrate, the quartz substrate has an incident end face for receiving and transmitting incident light and a corresponding exit end face, the exit end face of the quartz substrate has a micro-nano structure periodic array with a gradually changing morphology, the micro-nano structure periodic array includes a plurality of micro-nano structure units; the micro-nano structure units of the exit end face are filled with a transparent thin film material with a high refractive index to form a solid micro-nano structure periodic array.

10. The optical device according to claim 9, characterized in that The optical device is a solar-blind ultraviolet image intensifier.

Citation Information

Patent Citations

  • Grating type near-infrared anti-reflection optical element and preparation method and application thereof

    CN113238309A

  • Silicon carbide nano hollow column array and solar blind ultraviolet detector based on same

    CN115939261A

  • Silicon-based gallium oxide heterogeneous solar blind photoelectric sensor structure

    CN117878180A

  • Deep ultraviolet LED device and preparation method thereof

    CN118538840A

  • Solar-blind ultraviolet photoelectrochemical light detector and product thereof

    WO2021104528A1